Wellmania : extreme misadventures in the search for wellness - Delaney, Brigid (Greystone Books, 2018)
An in-depth, laugh-out-loud exploration of the best and worst of the wellness industry. Longtime journalist Brigid Delaney tackles the good, the bad, and the just-a-little-ridiculous of the wellness industry, using herself as the guinea pig. Writing with self-deprecating wit and refreshing honesty, she sorts through the fads and expensive hype to find out what actually works, asking: what does all this say about us? Is total wellness even possible?